Anticancer properties and mechanism insights of α-hederin - Belmehdi, Omar; Taha, Douae; Abrini, Jamal; Long, Chiau Ming *; Khalid, Asaad; Abdalla, Ashraf N.; Algarni, Alanood S.; Hermansyah, Andi; Bouyahya, Abdelhakim (Elsevier, 2023)
α-Hederin is a natural bioactive molecule very abundant in aromatic and medicinal plants (AMP). It was identified, characterized, and isolated using different extraction and characterization technologies, such as HPLC, LC-MS and NMR. Biological tests have revealed that this natural molecule possesses different biological properties, particularly anticancer activity. Indeed, this activity has been investigated against several cancers (e.g., esophageal, hepatic, breast, colon, colorectal, lung, ovarian, and gastric). The underlying mechanisms are varied and include induction of apoptosis and cell cycle arrest, reduction of ATP generation, as well as inhibition of autophagy, cell proliferation, invasion, and metastasis. In fact, these anticancer mechanisms are considered the most targeted for new chemotherapeutic agents’ development. In the light of all these data, α-hederin could be a very interesting candidate as an anticancer drug for chemotherapy, as well as it could be used in combination with other molecules already validated or possibly investigated as an agent sensitizing tumor cells to chemotherapeutic treatments.